Does Students` Professional and Entrepreneurial Experience Affect Business Model Creation? Quantitative Research in Germany and Poland - Jakub DRZEWIECKI (Communications of International Proceedings, 2025)
The goal of the article is to provide insight into the impact of students` professional and entrepreneurial experience on four crucial aspects of business model creation: sources of inspiration for the business model idea, the process of business model creation, the characteristics of the teamwork when designing business model and the final result of the work (the Business Model Canvas for a future business). Overall, 152 bachelor students were researched between October 2022 and June 2024 in Germany and Poland. Research enabled to indicate eight variables distinguish between experienced and non-experienced students. Particularly, students who possessed both types of experience were more likely to be inspired by an already existing business and focus on customer / client problem. They were also the only group that organized the process of working on the project by choosing a team leader. Students with both professional and entrepreneurial experience were also more likely to assign team roles. Furthermore, this group was the only one that analysed both profitability and feasibility of their future business. Lastly, this group was most aware of the Value Proposition impact on other elements of the BMC.
Keywords: business model; experience; Business Model Canvas; entrepreneurship.